2022
DOI: 10.1097/apo.0000000000000571
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic Patients With Rosacea Increase the Risks of Diabetic Macular Edema, Dry Eye Disease, Glaucoma, and Cataract

Abstract: Purpose: Inflammation plays a role in diabetic eye diseases, but the association between rosacea and eye diseases in patients with diabetes remains unknown. Design: This retrospective cohort study used claims data from the National Health Insurance Research Database in Taiwan to investigate the association between rosacea and eye diseases in patients with diabetes. Materials and Methods: Taiwanese patients diagnosed as having diabetes mellitus between January 1, 1997, and December 31, 2013, and using any h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…The contemporary human lifestyle is thought to be one of the main causes of numerous health disorders, such as diabetes mellitus, which can impair functioning of critical human body organs, such as the kidneys, heart, and eyes. Prolonged diabetes can lead to eye disorders and diseases, including Diabetic Retinopathy (DR), Diabetic Maculopathy (DM), and glaucoma [1]. These eye diseases are the leading An Efficient System for Diagnosis of Human Blindness Using Image-Processing and Machine-Learning Methods causes of blindness worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…The contemporary human lifestyle is thought to be one of the main causes of numerous health disorders, such as diabetes mellitus, which can impair functioning of critical human body organs, such as the kidneys, heart, and eyes. Prolonged diabetes can lead to eye disorders and diseases, including Diabetic Retinopathy (DR), Diabetic Maculopathy (DM), and glaucoma [1]. These eye diseases are the leading An Efficient System for Diagnosis of Human Blindness Using Image-Processing and Machine-Learning Methods causes of blindness worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Ocular rosacea can be overlooked by physicians [9] because the severity of clinical symptoms and signs of ocular rosacea do not usually correlate with those of facial rosacea [10]. Nevertheless, ocular rosacea is often comorbid in patients with facial rosacea, and some studies have confirmed the possible association of various ophthalmologic disorders other than manifestations of ocular rosacea in patients with rosacea [11,12].…”
Section: Introductionmentioning
confidence: 99%